QUR'ANIC BUSINESS: STUDY THE VERSES OF BUYING AND BUYING FROM THE INTERPRETATION OF AL-MUNIR'S PERSPECTIVE BY WAHBAH AL-ZUHAILI - Muhammad Arwani Rofi'i (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2025)
This study aims to uncover the principles of Qur'anic business through an examination of buying and selling verses in the Quran, utilizing the perspective of Tafsir al-Munir by Wahbah al-Zuhaili. The core issue addressed is the understanding of ethical business principles in Islam as contained in the Quran, particularly in the context of buying and selling transactions. The problem-solving method employed is a thorough analysis of Quranic verses related to buying and selling, as explained in Tafsir al-Munir. The study finds that in buying and selling transactions, the Quran emphasizes justice, prohibits usury, emphasizes mutually agreed-upon transactions, and underscores the ethics of trading. The Qur'anic business principles, when analyzed through Tafsir al-Munir, provide a strong foundation for fair, transparent, and ethical business practices in Islam. The emphasis on justice emphasizes the need to consider the interests of all parties in transactions. The prohibition of usury indicates the importance of avoiding practices that harm others. Mutually agreed-upon transactions emphasize transparency and voluntary agreements. Ethics in trading underscores the need to maintain honesty, trustworthiness, and the quality of goods traded. The conclusion drawn from this study is that understanding and implementing Qur'anic business principles in modern business practices can bring significant benefits, not only to the businesses themselves but also to society at large. This study makes a significant contribution to understanding how Islamic principles can be applied in modern business practices to achieve sustainable goals and benefit society at large.